Shewanella algae Peritonitis in Patients on Peritoneal Dialysis. Issue 5 (September 2016) - Shanmuganathan, Malini; Goh, Bak Leong; Lim, Christopher; NorFadhlina, Zakaria; Fairol, Ibrahim
Patients with peritonitis present with abdominal pain, diarrhea, fever, and turbid peritoneal dialysis (PD) fluid. Shewanella algae peritonitis has not yet been reported in PD patients in the literature. We present the first 2 cases of Shewanella algae peritonitis in PD patients. Mupirocin cream is applied on the exit site as prophylactic antibiotic therapy.